PELATIHAN AKUTANSI SISTEM PEMBUKUAN DIGITAL DALAM PENERAPAN SIKLUS AKUTANSI PADA UMKM DI DESA GELELUNGI KABUPATEN ACEH TENGAH - Bambang Surahman; Elisa Khairani; Amru Bin AS; Sabri Sabri (Bajang Institute, 2023)
The purpose of this community service activity is to assist Micro, Small and Medium Enterprises (MSMEs) in making digital accounting books in implementing the accounting cycle for MSMEs by using a digital accounting application, namely